2019
DOI: 10.1007/s11606-019-05205-1
|View full text |Cite
|
Sign up to set email alerts
|

ECHO Care: Providing Multidisciplinary Specialty Expertise to Support the Care of Complex Patients

Abstract: BACKGROUND: Programs for high-need, high-cost (HNHC) patients can improve care and reduce costs. However, it may be challenging to implement these programs in rural and underserved areas, in part due to limited access to specialty consultation. AIM: Evaluate the feasibility of using the Extension for Community Health Outcomes (ECHO) model to provide specialist input to outpatient intensivist teams (OITs) dedicated to caring for HNHC patients. SETTING: Weekly group videoconferencing sessions that connect multid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The program showed successful results as the sustained virologic responses achieved by those patients treated in primary care settings under the guidance of ECHO were similar to those observed when patients were treated by specialists [6]. Since then, the ECHO project expanded to many states in the U.S. as well as in many other countries and was also adopted by other medical specialties [7,8]. Currently, this type of care is considered a vital tool for the goal of global elimination of HCV infection [9].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 78%
“…The program showed successful results as the sustained virologic responses achieved by those patients treated in primary care settings under the guidance of ECHO were similar to those observed when patients were treated by specialists [6]. Since then, the ECHO project expanded to many states in the U.S. as well as in many other countries and was also adopted by other medical specialties [7,8]. Currently, this type of care is considered a vital tool for the goal of global elimination of HCV infection [9].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 78%
“…46 One study found mortality reduction at 1 year of a relative 42% (6.2% vs. 10.6% for controls). 47,48 A Swedish intervention study found reduced mortality risk (HR-0.66) over 24 months, 49 and another found reduced relative mortality of 45% (16% vs 29%) at 6months, 50 among older frail patients. Thus, our findings are not unprecedented.…”
Section: Discussionmentioning
confidence: 99%
“…Primary care physicians within academic medical centers would seem well positioned to manage patients with multimorbidity given their need for specialty care and interdisciplinary coordination. 17,18 However, designing this type of practice for an academic environment poses specific challenges. Physicians at academic centers are already keenly aware of the need to juggle clinical responsibilities with scholarship and teachingserving the faculty mission of advancing medical knowledge through education and research.…”
mentioning
confidence: 99%